Distributed Information Flow Verification Framework for the Composition of Service Chain in Wireless Sensor Network - Ning Xi; Jianfeng Ma; Cong Sun; Yulong Shen; Tao Zhang (International Journal of Distributed Sensor Networks)
Dynamic service composition provides us with a promising approach to cooperate different sensor nodes in WSN to build complex applications based on their basic functions. Usually multiple nodes located in different regions provide data with different security levels, and it is critical to ensure the security of the information flow in the composite services. However, the energy-limited nature of sensor nodes in WSN poses a significant challenge for the centralized information flow verification with which the verification node needs to consume lots of computation and network resources. In this paper, we specify the security constraints for each service participant to secure the information flow in a service chain based in the lattice model and then present a distributed verification framework that cooperates different service participants to verify their information flow policies distributively. The evaluation results show a significant decrease on the verification cost of the single verification node, which provides a better load balance in each sensor node.